The Grammar of Javanese in The Bawean Madurese - Tjahyadi, Indra; Andayani, Sri (Critical Review of English-Arabic World Journal, 2022)
Bawean language is identified as a hybrid language. Many languages influence the vocabulary of the Bawean language. At least, there are Madurese, Javanese, Malay, Buginese, etc. However, most of Bawean vocabulary are from Madurese. In its distribution to surroundings areas, Madurese is a language that is not easy to change its grammar. Even, it tends to influence the native local language of the people, as the Pandalungan Javanese that is used by the people in the north coast areas of East Java. There, the Grammar of Madurese influences much the Javanese, that is the native language of Javanese people. In other case, it occurs differently in Bawean language. Here, the language that most of the vocabulary comes from Madurese is influenced by the Javanese grammar. It makes the Bawean language different from the Madurese. By doing qualitative descriptive study that compares the significant grammar features of Madurese and Javanese that influence Bawean language, this study is conducted. The data are collected by using observation and interview method. Then, they are analyzed by the identity methods. The study finds that the Madurese Bawean is different from the native Madurese in terms of reduplication and affixation. Although most of the Bawean vocabulary come from Madurese, not all of the Madurese reduplication and affixation Javanese involve the Bawean ones. The Javanese also takes important part in the grammar of Bawean Madurese.